Aportaciones a la flora de Galicia (España), 16 - Silva-Pando, Francisco Javier; Baladrón González, Juan; Pino Pérez, Rubén; Pino Pérez, Juan José (UMA Editorial, 2025)
La revisión de material de Cormophyta conservado en los herbarios LOU y recolecciones recientes en Galicia han revelado seis novedades florísticas para la región: Pteris multifida, P. cretica, Ranunculus trichophyllus subsp. eradicatus, Sisymbrium austriacum subsp. contortum, Narcissus × medioluteus e Isolepis pseudosetacea, y la confirmación de poblaciones de Salix purpurea y Geranium lanuginosum en Galicia. De los ocho táxones tratados, cinco se corresponden con plantas consideradas autóctonas y otras tres, exóticas.

A review of Cormophytamaterial held in LOU herbaria and recent collections in Galicia has revealed floristic novelties for the region: Pteris multifida, P. cretica, Ranunculus trichophyllussubsp. eradicatus, Sisymbrium austriacumsubsp. contortum, Narcissus × medioluteus, and Isolepis pseudosetacea, and confirmed populations of Salixpurpureaand Geraniumlanuginosumin Galicia. Of the eight taxa discussed, five correspond to plants considered native and three are exotic
Contributions to the flora of Galicia (Spain), 16
Keywords: Plantas - Clasificación; Fitogeografía; Plantas extrañas - Galicia; Plantas autóctonas; Exóticas; NO España; Taxonomía; Corología